Influence of age on the diagnostic value of coronary artery calcium score for ruling out coronary stenosis in symptomatic patients. (3rd October 2022) - Lopes, P; Albuquerque, F; Freitas, P; Goncalves, P A; Presume, J; Guerreiro, S; Abecasis, J; Santos, A C; Saraiva, C; Mendes, M; Marques, H; Ferreira, A
Abstract: Background: The 2021 Guideline for the Evaluation of Chest Pain supports the use of coronary artery calcium (CAC) score as a reasonable first-line test to identify patients with a low likelihood of obstructive coronary artery disease (CAD) who may not require additional testing (class IIa, LOE B). However, a recent study from a large cohort of Northern European patients raised concerns about the added diagnostic value of CAC=0 in younger patients. The aim of this study was to assess the influence of age on the value of CAC=0 in symptomatic patients undergoing coronary computed tomography angiography (CCTA). Methods: We conducted a two-center cross-sectional study assessing symptomatic patients with suspected CAD who underwent CAC score and CCTA. Key exclusion criteria were age <30 years, known CAD, suspected acute coronary syndrome, or symptoms other than chest pain or dyspnea. Pretest probability of obstructive CAD was calculated based on age, sex and symptom typicality, according to the guideline-recommended method. Obstructive CAD was defined as any luminal stenosis ≥50% on CCTA. The diagnostic likelihood ratios and negative predictive values (NPV) were used to assess the diagnostic value of a CAC score of 0 to rule out obstructive CAD. Results: A total of 2043 patients (mean age 60±11 years, 60% women) of whom 990 (48.5%) had a CAC score of 0 were included in the analysis. Symptom characteristics were: 38% non-anginal chest pain, 30% atypical angina, 19% dyspnea, and 13% typical chest pain. Overall, the prevalence of obstructive CAD was 12.8% (n=262). Pretest probability of obstructive CAD increased progressively with age, from 6.0% in patients young than 50 years to 20.7% in those 70 years or older. Contrariwise, the prevalence of patients with a CAC score = 0 decreased from 77% in patients younger than 50 years, to 26% in those who where 70 years or older. The added diagnostic value of a CAC score = 0 was lower in younger patients, with negative likelihood ratios ranging from 0.36 (64% decrease in the likelihood of CAD) in patients younger than 50 years, to 0.09 and 0.10 (∼90% decrease in the likelihood of CAD) in those aged 60–69 years and 70 years or older, respectively – Figure 1. Despite this, the prevalence of obstructive CAD among patients with a CAC score = 0 was low across all age groups: 2.4% (i.e., NPV = 97.6%) in those younger than 50 years, 3.0% (NPV = 97.0%) among those aged 50–59 years, 1.5% (NPV = 98.5%) in patients between 60 and 69 years, and 2.0% (NPV = 98.0%) among those 70 years or older. Conclusions: In a cohort of symptomatic patients undergoing CCTA for suspected CAD, the added diagnostic value of a CAC score of zero decreases significantly at younger ages. However, this "diminishing return" of CAC in younger patients if offset by their lower pretest probabilities, yielding high negative predictive values independently of age. Funding Acknowledgement: Type of funding sources: None.